Charge Geometry Effects on Pressure Waveforms in a Shock Tube - Kyle Perry; Braden Lusk; Joshua Hoffman (International Society of Explosives Engineers, 2010)
Shock tubes are used to simulate large-scale arena explosions without the use of full-scale arena sites that utilize large quantities of explosives. Instead, small explosive charges can be used to drive shock tubes. When this is done, the geometries of the explosive charges can alter the resulting pressure time curve. A common geometry chosen for the explosive charge is a sphere in order to be congruent with the spherical shockwave that emanates symmetrically in three dimensions from the detonation point. This paper reports on the findings from experiments that study the effects of altering the charge geometries and explosive types while keeping the TNT equivalency constant. Peak pressures and durations were affected by these changes. Directional phenomena are exaggerated by the use of certain charge shapes and detonation points. The speed of the detonation front in the explosive being greater than the speed of the shockwave in air played a critical role in the resulting pressure time waveforms. Waveform manipulation can be used to generate job specific waveforms that ultimately benefit the shock tube operators and their clients.